Assistance in Developing a Simple Internal Audit Checklist to Support Audit Completion at Kopii Kawaii - Wahyuni; Mellisyah; Musdalifah Hasmal; A. Megawati Junaedi; Siti Athirah Asmarani; Lilis Sukanda (www.amertainstitute.com, 2026)
Effective internal control is essential for strengthening accountability, reducing operational risks, and supporting sustainable financial governance in Micro, Small, and Medium Enterprises (MSMEs). However, many MSMEs lack practical internal audit instruments that enable systematic monitoring of cash, sales, inventory, purchasing, and administrative documentation. This community engagement program aimed to assist Kopii Kawaii, a coffee shop in Makassar, Indonesia, in developing and implementing a simple internal audit checklist to support audit completion and strengthen internal control practices. The program employed a participatory mentoring approach comprising preliminary observation, interviews, problem identification, checklist development, simulation, implementation, evaluation, and follow-up assistance. Data were obtained through direct observation, interviews with the business owner and employees, transaction document reviews, and operational verification. The developed checklist covered five key areas: inventory, sales, cash, purchasing, and administrative documentation. Implementation demonstrated improvements in transaction verification, cash reconciliation, inventory monitoring, document organization, and employee awareness of internal control procedures. The checklist also facilitated the identification and documentation of operational weaknesses and supported the preparation of evidence required for audit completion. Furthermore, the mentoring process encouraged the business owner and employees to conduct routine self-evaluation and strengthen accountability in daily operations. The findings demonstrate that a simplified internal audit checklist can serve as a practical, low-cost governance instrument for MSMEs with limited resources. This approach provides a replicable model for improving internal control, financial transparency, audit readiness, and organizational sustainability through university–community collaboration.